Leveling Up English Writing Skill: The Role of Gamification in Language Education - Satriani Satriani; Rafi’ah Nur; Salasiah Ammade; Ammang Latifa; Siti Hajar Larekeng (Hasanuddin University, 2024)
Integrating game aspects into non-gaming environments, or